Chronic Active Antibody-mediated Rejection in Kidney Transplant Recipients: Treatment Response Rates and Value of Early Surveillance Biopsies. Issue 9 (4th August 2022) - Aziz, Fahad; Parajuli, Sandesh; Jorgenson, Margaret; Garg, Neetika; Manchala, Venkata; Yousif, Elsadiq; Mandelbrot, Didier; Hidalgo, Luis; Mohamed, Maha; Zhong, Weixiong; Djamali, Arjang
Abstract : Background: There is limited information on the value of short-term invasive and noninvasive monitoring in kidney transplant recipients (KTR) undergoing therapy for chronic active antibody-mediated rejection (cAMR). Methods: We describe response rates in patients with cAMR receiving pulse steroids/IVIG ± rituximab 3-mo after index biopsy. Results: The study included 82 consecutive KTR. Mean time from transplant to cAMR was 10 y. Mean peritubular capillaritis (ptc), glomerulitis (g), microvascular inflammation (MVI), C4d, and cg Banff scores were 1.1, 2.1, 3.2, 0.2, and 2, respectively. Mean estimated glomerular filtration rate (eGFR) and urine protein creatinine (UPC) ratio were 38 mL/min and 1.6 g/g, respectively. Thirty (37%) patients lost their allograft during the mean follow-up of 2.4 y. In patients treated with pulse steroids/IVIG (n = 41), response rates for eGFR, UPC, donor-specific antibodies (DSAs), and MVI were 27%, 49%, 7%, and 19%, respectively. In the pulse steroids/IVIG/rituximab group, response rates were 66%, 61%, 20%, and 69%, respectively. Univariate analysis identified response in eGFR (HR = 0.03; P = 0.001; 95% CI, 0.004-0.26), UPC (HR = 0.38; P = 0.01; 95% CI, 0.18-0.82), and DSA (HR = 0.11; P = 0.004; 95% CI, 0.02-0.49) as predictors of graft survival. Multivariate analysis only retained eGFR response (HR = 0.12; P = 0.01; 95% CI, 0.02-0.64). Conclusions: In cAMR, short-term response to treatment for kidney function and DSA was associated with graft survival, but the role of early surveillance biopsies needs further evaluation.